THE EXPOSURE FOR POPULATIONS OF THE RUSSIAN FEDERATION DUE TO THE CHERNOBYL ACCIDENT AND MAIN DIRECTIONS OF FURTHER WORK IN THE COMING PERIOD - G. J. Bruk; A. B. Bazykin; A. N. Barkovsky; A. A. Bratilova; A. Yu. Vlasov; Yu. N. Goncharova; A. V. Gromov; T. V. Jesko; S. A. Ivanov; M. V. Kaduka; O. S. Kravtsova; V. V. Kuchumov; et al. (Радиационная гигиена)
The article discusses the issues associated with the current exposure of the population of 14 regions of Russia due to the Chernobyl accident, identified tasks facing Rospotrebnadzor today. The article describes criteria and requirements for ensuring of the mechanism of the transition of settlements from the conditions of a radiation accident to the public normal conditions.